Nurturing Wireless Communication: Coalition of Cognitive Radio with Li-Fi - Ridhima, Ridhima (International Journal of Computer Sciences and Engineering, 2025)
Evolution of surplus gadgets accessing web facilities has eventually actuated the resource congestion. Several alluring data grabbing techniques are utilized with their respective pros and cons. The paper administers a concept which is based on the integration of the Li-Fi with the Cognitive Radio technology, diversifying the wireless communication with hiking spectrum utilization and vast capacity. The concept adheres to improve the multi-user communication by relying on the use of both the optical as well as the radio frequency spectrums in a communicating network which is more effective instead of using Li-Fi or Cognitive Radio independently.